Circulating miR-378 and miR-451 in serum are potential biomarkers for renal cell carcinoma - Redova, Martina; Poprach, Alexandr; Nekvindova, Jana; Iliev, Robert; Radova, Lenka; Lakomy, Radek; Svoboda, Marek; Vyzula, Rostislav; Slaby, Ondrej (Journal of translational medicine, 2012)
BACKGROUND: There is no standard serum biomarker used for diagnosis or early detection of recurrence for renal cell carcinoma (RCC) patients. MicroRNAs (miRNAs) are abundant and highly stable in blood serum, and have been recently described as powerful circulating biomarkers in a wide range of solid cancers. Our aim was to identify miRNA signature that can distinguish the blood serum of RCC patients and matched healthy controls and validate identified miRNAs as potential biomarkers for RCC. METHODS: In the screening phase of the study, blood serum of 15 RCC patients and 12 matched healthy controls were analyzed by use of the TaqMan Low-Density Arrays enabling parallel identification of expression levels of 667 miRNAs through qRT-PCR-based approach. In the validation phase, identified miRNAs were further evaluated on the independent group of 90 RCC patients and 35 matched healthy controls by use of individual qRT-PCR assays and statistically evaluated. RESULTS: We identified 30 miRNAs differentially expressed between serum of RCC patients and healthy controls: 19 miRNAs were up-regulated and 11 miRNAs were down-regulated in RCC patients. MiR-378, miR-451 and miR-150 were further evaluated in the independent group of patients, and two of them were successfully validated: levels of miR-378 were increased (p = 0.0003, AUC = 0.71), miR-451 levels were decreased (p < 0.0001, AUC = 0.77) in serum of RCC patients. Combination of miR-378 and miR-451 enable identification of RCC serum with the sensitivity of 81%, specificity 83% and AUC = 0.86. CONCLUSIONS: Circulating miRNAs in serum are promising biomarkers in RCC.
Keywords: Gene Expression Regulation, Neoplastic; nádory ledvin; Male; plošný screening; Cluster Analysis; MicroRNAs; ROC Curve; karcinom z renálních buněk; mikro RNA; regulace genové exprese u nádorů; Adult; shluková analýza; Kidney Neoplasms; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; stanovení celkové genové exprese; reprodukovatelnost výsledků; Reproducibility of Results; Gene Expression Profiling; Mass Screening; lidé; ženské pohlaví; studie případů a kontrol; Biomarkers, Tumor; Humans; Carcinoma, Renal Cell; Female; ROC křivka; lidé středního věku; nádorové biomarkery; Middle Aged